International Law to Understand Russia’s Invasion of Ukrainian 2022 : between Self-Defence and Deficiency - Hemriyantton, Bobbi; Wirajuda, Muhammad Hadianto; Herman, Erry (East Asian Journal of Multidisciplinary Research, 2024)
The method and material section will discuss the stages of international law and political studies, identifying problems in finding data and analyzing the water, and then reporting the findings (Harper, 2011). We can reiterate that this study was carried out to find understanding and rationality in international law regarding Russia's attack on the Ukrainian state, which recently has attracted world attention to whether Russia's actions were between self-defense or attack. We have conveyed under the title of the study understands the Russian military attack on sovereignty which has recently become scorching news that beats other news. So the conclusion is that we have comprehensive information on why Russia attacked Ukraine in terms of cultural history and the current reality of each other, maintaining the integrity and tranquility of each other's country.